The Difference Between a Junior High School Student’s Stress Level Applying a Full day and Half Day School System - Fitri Ayu Fitri (Jurnal Medika Hutama, 2022)
Aim: Students’ inability to manage their study time will cause them to experience stress. The study was aimed to determine the difference in stress levels among junior high students attending either full day school or half day school in Rokan Hulu regency. Method: The study used quantitative method with comparative study using cross sectional approach. The sampling used in this study were the minimum samples. 30 junior high school students took partin this study as respondents, which were chosen using inclusion criteria. Then the data were analyzed using bivariate of Mann-Whitney. Result: Regarding the stress levels of secondary school students attending full day school , 26 respondents (86,7%) experienced medium stress levels, while 4 respondents (13,3%) were in the low stress levels. On the other hand, among students attending half day school, 18 respondents (60%) were in the low stress levels, and 12 respondents (40%) were in medium stress levels. The statistical test results showed the there was a significant difference between junior high school students attending full day school and those attending half day school, with p-value 0,000 < alpha (0,05). The stress levels of junior high school students attending full day school were medium, while those attending half day school were low. Conclusion:. Mental health nurses within the community are expected to provide necessary education and intervention for students, while school parties should have relevant strategies to apply during learning process, for example: learning together outside the classroom, so they can enjoy the process, be less bored, and avoid from stress.